Effects of growth conditions on siderophore producing bacteria and siderophore production from Indian Ocean sector of Southern Ocean. (23rd January 2019) - Sinha, Alok K.; Parli Venkateswaran, Bhaskar; Tripathy, Sarat C.; Sarkar, Amit; Prabhakaran, Sabu
Abstract : Iron is an important element for growth and metabolism of all marine organisms, including bacteria. Most (99.9%) of iron in oceans are bound to organic ligands like siderophores and siderophore‐like compounds. Distribution of bioavailable iron mainly depends on pH and temperature of the ocean. Due to global warming and ocean acidification, bioavailability of iron may alter and in turn effect the response of marine bacteria. In this study, we investigated the effect of growth conditions like pH, temperature, and iron (III) concentrations on growth and siderophore production in selected heterotrophic bacteria isolated from waters around Kerguelen Islands (KW) and Prydz Bay (PB). Microcosm experiments were carried out on two KW‐isolates ( Enterococcus casseliflavus and Psychrobacter piscatorii ) and five PB‐isolates ( Pseudoalteromonas tetraodonis, Bacillus cereus, Psychrobacter pocilloporae, Micrococcus aloeverae, and Pseudomonas weihenstephanensis ) which produced either hydroxamate‐type or catecholate‐type siderophores. Increasing iron concentrations (10 nM to 50 μM) increased the growth rate of all isolates while siderophore production (% siderophore) generally reduced at higher iron concentration. Siderophore production peaked at early log phase, probably in response to higher iron‐demand. Temperature and pH experiments showed that most isolates produced more siderophore at 15 and 25 °C temperature and pH 8.5. These results reveal that in future ocean conditions (warmer and acidified waters), bacterial growth and siderophore production may get affected and thereby influencing iron uptake and associated biogeochemical processes.